Electron Scattering from Stable and Exotic Li Isotopes - Hameed, ameen; Ridha, Arkan R. (Iraqi Journal of Science, 2024)
The nuclear shell model was used to investigate the bulk properties of lithium isotopes (6,7,8,9,11Li), i.e., the ground state density distributions and C0 and C2 components of charge form factors. The theoretical treatment was based on supposing that the Harmonic-oscillator (HO) potential governs the core nucleons while the valence nucleon(s) move through Hulthen potential. Such assumptions were applied for both stable and exotic lithium isotopes. The HO size parameters (  and ), the core radii ( ) and the attenuation parameters (  and ) were fixed to recreate the available empirical size radii for lithium isotopes under study.